Educational technologies and tools: use of digital games with students diagnosed with ADHD – literature review (Research, Society and Development, 2022)
The present study discusses the importance of the benefits of the use of technologies in the education network. It highlights the divergence of students' behavior, as well as their learning complexities. In this case, hyperactivity is an element of Attention Deficit Hyperactivity Disorder (ADHD) that arises in childhood and can accompany the permanent individual, it is a neurobiological disorder of genetic predisposition, with hyperactivity, restlessness and impulsivity as one of the main symptoms. Based on this, this study will be guided by the following problem: How do technologies impact the teaching-learning process of children with ADHD in the early years? In such a way, the present research is justified by the importance given to the social and educational perspectives that it will manage to facilitate for pedagogical practice and educational management. The present research project has the general objective to discuss the use of technology in learning with elementary school children who have ADHD, presenting the following specific objectives: To know the methodologies applied in Teaching Learning with students diagnosed with ADHD, To analyze the pedagogical practice of the teacher with the use of technologies and highlight the pedagogical actions developed in the school environment with students diagnosed with ADHD. The present work is a bibliographic research that aims to analyze the theme regarding the aid of technology in the teaching-learning of students with ADHD in the early years.